Maternal and neonatal outcomes and prognostic factors in acute fatty liver of pregnancy. (September 2020) - Joueidi, Y.; Peoc'h, K.; Le Lous, M.; Bouzille, G.; Rousseau, C.; Bardou-Jacquet, E.; Bendavid, C.; Damaj, L.; Fromenty, B.; Lavoué, V.; Moreau, C.
Highlights: We analyzed acute fatty liver of pregnancy in a large multicenter cohort. Incidence of AFLP was estimated as one case for 7914 pregnancies. Increased prothrombin time is a risk factor of maternal complications. Infants born to mothers with ALFP should be screened for β-oxidation deficiency. Abstract: Objective: To report complications of Acute Fatty Liver of pregnancy (AFLP), a rare liver disease of pregnancy, and identify prognostic factors for mothers and children. Study Design: We conducted a retrospective descriptive study over 18 years in three French maternities. Demographic, clinical, biological data, and outcomes of patients and their infants were reviewed. Results: 142, 450 pregnancies from centers were studied. Eighteen patients with AFLP were identified The prevalence of AFLP was estimated as 1/7, 914 pregnancies. Prolonged prothrombin time was identified as a risk factor of maternal complications (OR = 0.86, p = 0.0493). Gestational age at delivery was the only risk factor associated with fetal or neonate complications (OR = 0.37, p = 0.0417). One boy died of previously undiagnosed β-oxidation deficiency at eight months. Conclusion: In AFLP, prothrombin time must be carefully monitored to anticipate major maternal complications. Infants born to mothers with ALFP should be screened as early as possible for mitochondrial fatty acid oxidation deficiency.